Daddy`s cleaning service / Dionysia Jimmy... [et al.] - Jimmy, Dionysia; Shafie, Eddie; Saiban, Mohd Noramin; Ismail, Sharif Hafify (2012)
This business plan is prepare for the DADDYS cleaning service for the better management and as the document to refer with during the business operation. Future more, this business plan are prepare for the planning and establishment for this business. In addition, this business plan also prepare for the guideline of this business for the current and future prospect of this business and the service industry.